2010
DOI: 10.1093/cvr/cvq028
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A-induced nitration of tyrosine 34 MnSOD in endothelial cells: role of mitochondrial superoxide

Abstract: We propose that CsA induced endothelial damage may be related to increased mitochondrial superoxide formation and subsequent peroxynitrite-dependent nitroxidative damage, specifically targeting MnSOD. The inactivation of this key antioxidant enzyme by tyrosine nitration represents a pathophysiological cellular mechanism contributing to self-perpetuation and amplification of CsA-related vascular toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…Hence, even at saturating levels of cGMP for the non-nitrated enzyme, the kinase activity seems to be lower in the nitrated protein. Our findings are also in agreement with other studies that have also shown that the negative charge imparted by nitration alters the hydrogen bonding network between the substrate and protein in such enzymes as manganese superoxide dismutase (46), glutathione reductase (47), and prostacyclin synthase (48). However, it should be noted that our results appear to be contradictory to a previous study.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, even at saturating levels of cGMP for the non-nitrated enzyme, the kinase activity seems to be lower in the nitrated protein. Our findings are also in agreement with other studies that have also shown that the negative charge imparted by nitration alters the hydrogen bonding network between the substrate and protein in such enzymes as manganese superoxide dismutase (46), glutathione reductase (47), and prostacyclin synthase (48). However, it should be noted that our results appear to be contradictory to a previous study.…”
Section: Discussionsupporting
confidence: 87%
“…Peroxynitrite is well-established to inactivate MnSOD by nitrating a critical Tyr residue (Tyr 34) at the enzyme active site both in vitro and in vivo (102,137,141,163). A recent study also reported Tyr nitration of MnSOD and resultant inactivation of the enzyme upon exposure to NO (162).…”
Section: Mnsod Regulation Via Other Post-translational Modifications mentioning
confidence: 99%
“…Aza increases EC survival, 17 in contrast to sirolimus, which induces apoptosis, causing the thrombotic problems in sirolimus-coated coronary stents, 18 or cyclosporine A that is toxic to ECs and provokes vasculopathy. 19 We and others have previously shown that Aza maintains the contractile phenotype of smooth muscle cells 20,21 and has an anti-inflammatory effect in macrophages 22 and T cells. 23 Thus, Aza seems a good candidate drug to treat inflammation and protect the vessel wall.…”
mentioning
confidence: 92%